PARQUE CILIAR DO RIBEIRÃO ONÇA: O IMAGINÁRIO DAS ÁGUAS URBANAS NA CONSTRUÇÃO DO ESPAÇO PÚBLICO COMUNITÁRIO EM BELO HORIZONTE/MG - Moreira, Carla Wstane de Souza (2021)
Modern cities have been risen from a hidraulic and techno channelization of rivers and streams unleash several socioenvironmental and economical problems different parts of the city, like major floods. Considering the river itself as a life quality measure that funds the Projeto Manuelzão ethos, the capillarity of the river basin thrives emerging movements throughout the territory. Concerning the Philosophies of Difference, this thesis discusses the importance of a conceptual framework that allows the cartography of democratic becoming, and also allowing new openings that another water culture is possible. COMUPRA experiences and Deixem o Onça Beber Água Limpa movement are displayed as possibilities of living cities and living rivers mentality, in one of the most vulnerable areas of Belo Horizonte, the Baixo Onça. That environment is uplifted in the present research as a true possibility of political engaging and also acknowledgment of the multiplicites. Some elements provided by Lefebrve’s Theory of the Production of Space such as Practice, Representations of Space and Representational Space are key to organize a spatial lecture of the cilliary and common park of the Onça River.